2016
DOI: 10.1002/cctc.201600492
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Mesoporous Materials as Supports for Stable Iron Catalysts in the Fischer–Tropsch Synthesis of Lower Olefins

Abstract: The Fe‐catalyzed Fischer–Tropsch to olefins (FTO) synthesis is a non‐oil‐based route for the production of C2–C4 olefins. The understanding of the interplay between the catalytically active species, promoters, and support materials has improved over the last years, but the nanostructures of the various supports used are often not comparable. Several ordered mesoporous materials with a comparable pore size and pore symmetry are used as model supports for Fe‐based FTO catalysts. Ammonium iron citrate is used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 40 publications
3
30
0
Order By: Relevance
“…Although Co and Fe are the commonly used Fischer–Tropsch metals, nanostructured iron (carbide) catalysts are applied in the high‐temperature FTO process because of their low methane selectivity, high abundance, high water gas shift activity, and low cost . Although numerous species (iron oxides, metallic iron, iron carbides, and their combinations) can play a role in the FTO process, it has been shown that iron carbides are the catalytically active phase . Recently, it was foundthat especially the addition of a combination of Na and S promoters can suppress methane formation and increase the activity of FTO catalysts at the same time …”
Section: Introductionmentioning
confidence: 99%
“…Although Co and Fe are the commonly used Fischer–Tropsch metals, nanostructured iron (carbide) catalysts are applied in the high‐temperature FTO process because of their low methane selectivity, high abundance, high water gas shift activity, and low cost . Although numerous species (iron oxides, metallic iron, iron carbides, and their combinations) can play a role in the FTO process, it has been shown that iron carbides are the catalytically active phase . Recently, it was foundthat especially the addition of a combination of Na and S promoters can suppress methane formation and increase the activity of FTO catalysts at the same time …”
Section: Introductionmentioning
confidence: 99%
“…Despite novel catalysts including OX‐ZEO and cobalt carbide have been reported to obtain a high lower olefins selectivity with a relative lower CO conversion, iron‐based catalysts still arouse much more attention because of their low cost, tolerance for CO/H 2 ratio, resistance to contaminants, and feasibility in industry. Generally, particle size of Fe species, promoter, Fe precursor and support should be taken into account to design iron‐based FTO catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…S5, ESI †). All catalysts show the typical multi-step reduction profile 9 for carbonsupported iron catalysts in presence of Na/S promoters and the overall hydrogen consumption is comparable for all samples. However, the hydrogen consumption peaks are shifted to higher temperatures for the Fe/Na/S-C-Micro related to the larger iron particle size and their restricted accessibility caused by the narrow pore system of this catalyst.…”
mentioning
confidence: 81%
“…[13][14][15] The most widely applied method for the preparation of carbon-supported FTO catalysts is deposition of the iron precursor (most often by solution impregnation) on the surface of a pre-formed carbon material (e.g., carbon nanotubes, porous carbons, or carbon nanofibers) followed by drying and calcination. 7,9,12,14 However, this process can suffer from its non-continuous character and potentially inhomogeneous distribution of the active phase after drying and calcination. One-pot synthesis of iron/carbon catalysts by pyrolyzing mixtures of precursors of support and metal is one option to overcome this drawback.…”
Section: -10mentioning
confidence: 99%